Answer:
A
Explanation:
The explicit formula for a geometric sequence is
= a₁
![(r)^(n-1)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/ez8dud9slpmkhrs6kdah0v4b69qcdaapqa.png)
where a₁ is the first term and r the common ratio
Given the explicit formula
= 6
![(-(1)/(4)) ^(n-1)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/p46e1l2rm67e7fb4h0rbsbq1vrbed83tmc.png)
where a₁ = 6 and r = -
![(1)/(4)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/r8zl28n0vf0ogg71i3r53apxva24c1inf4.png)
A recursive formula allows any term in the sequence to be found by multiplying the previous term by r , thus
=
(-
with a₁ = 6 → A